An updated checklist of Orchidaceae for China, with two new national records - Zhou, Xiaoxu; Cheng, Zhiquan; Liu, Qiaoxia; Zhang, Junli; Hu, Aiqun; Huang, Mingzhong; Hu, Chao; Tian, Huaizhen (Phytotaxa, 2016)
In this study, an updated checklist of Orchidaceae for China is presented based on all recently available literature and online resources relevant to new taxa, national or regional new records, and new taxonomic papers. This checklist includes 208 genera and 1695 taxa. Additionally, two new national records for Orchidaceae from Yunnan, viz. Rhomboda lanceolata and Porpax elwesii, are reported with detailed morphological descriptions and illustrations.